(untitled) (Multidisciplinary Journal of Science and Technology, 2026)
This article presents a comparative linguocultural analysis of verbal and nonverbal lacunae in Japanese and Uzbek, with particular emphasis on the challenges they pose for translation and intercultural communication. The study aims to identify culturally specific gaps in verbal expressions and nonverbal behavior that lack direct equivalents across the two languages. Drawing on recent research in cultural linguistics, pragmatics, and translation studies, the analysis examines how linguistic and extralinguistic lacunae emerge from culturally embedded norms, values, and communicative conventions. Verbal and nonverbal examples from Japanese and Uzbek are analyzed with English translations provided in parentheses. The findings reveal that many lacunae arise from differences in social hierarchy, emotional restraint, collectivist versus community-based orientations, and culturally regulated nonverbal conduct. The study contributes to linguocultural theory and offers practical implications for translation practice and intercultural competence development.